I read those F O I L comments above, and I now understand it
But I'm not from an English speakign country, and have therefore not had any experience with F.O.I.L.
Very good, thumb for you sir.
TO THOSE WHO DONT GET IT:
(X-2)(X+2)
X times X = X[s] (squared)
X times +2 = 2X
-2 times X = -2X
-2 Times +2 = -4
X[s] + 2X -2X -4 = X[s] -4
Never heard of that **** .
We just learned that each addend should be multiplied with both of the other addends.
But that's a step we normally just skipped.
(a+b)^2=a^2+2ab+b^2